Guided Discovery Worksheet for Increasing Mathematical Creative Thinking and Self-Efficacy - Tripatika Yuliani; Sri Hastuti Noer; Undang Rosidin (International Journal of Trends in Mathematics Education Research, 2018)
This research development aimed to develop of worksheet based on guided discovery for increasing mathematical creative thinking and student’s self-efficacy. Development stage in this study is a preliminary study, planning, development of worksheet, worksheet validation, and field testing. The subject of this research is the students of class 10A3 and 10A5 MAN 1 Central Lampung in the Academic of 2017/2018. The data of this research were obtained by observation, interview, mathematicalcreative thinking ability test and self-efficacy scale. The result of the validity by subject matter expert and media expert showed that the worksheet is considered excellent. The Initial field testing results indicate that worksheet is included in either category. The field testing results showed that (1) the student’s mathematical creative thinking aspect was effective because seen from the N-Gain of 0,54 which included in the category of moderate improvement and (2) the student’s self-efficacy was effective because seen from the N-Gain of 0,36 which included in the category of moderate improvement. It can be concluded that worksheet based on guided discovery effective way to improve the mathematical creative thinking ability and student’s self-efficacy.